How to do things with narrative: cognitive and diachronic perspectives - Alber, Jan; Olson, Greta; Christ, Birte (Narratologia, 2018)
This volume combines narratological analyses with an investigation of the ideological ramifications of the use of narrative strategies. The collected essays do not posit any intrinsic or stable connection between narrative techniques and world views. Rather, they demonstrate that world views are inevitably expressed through highly specific formal strategies. This insight leads the contributors to investigate why and how particular narrative techniques are employed and under what conditions.
Keywords: Aufsatzsammlung; Festschrift; Erzähltechnik; Erzähltheorie